RANCANG BANGUN ANTENA HELICAL 1800 MHz UNTUK MEMPERKUAT PENERIMAAN SINYAL GSM (GLOBAL SYSTEM FOR MOBILE ) - Eko Puji Utomo . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2017)
Antenna is used to emit electromagnetic waves or receive electromagnetic waves. Acceptance using antenna will strengthen the signal gain according to the antenna capability itself. Gsm service providers (Global System for Mobile) with the limitations of the network it covers makes the need for strong signal gain strengthening. Antennahelical is one of the strengthening options of signal gain. In this final project designed helical antenna applied at frequency 1800 mhz. Helical antennas can be auxiliary media in strengthening the reception of gsm signals. The parameters to be used to determine the value of power reinforcement (Gain). The application used is gsm signal monitor software.   The test results and discussion in get the value of power reinforcement (gain) in telecommunication laboratory faculty of engineering tanjungpura university pontianak at morning 15 db, noon 31 db, and afternoon 13 db with average signal streangth at the time without using helical antenna that is -99.4 dbm in the morning, -98.8 dbm during the day, and -95.6 dbm in the afternoon with red signal indicator (poor). While using helical antenna is the average value of signal strength -88,2 dbm in morning with orange signal indicator (Fair), - 80,6 dbm daytime, and -80,4 afternoon with indicator of yellow signal ( good). While at jl.ujung pandang villa brata indah no.12 b power strength (Gain) at the morning of 27 db, noon 27 db, and afternoon at 13 db. With an average of signal strength at the time without using helical antenna is -95.8 dbm in the morning, -97.4 dbm during the day, and -101.6 dbm late afternoon with red signal indicator (poor). While using helical antenna is the average signal strength value of -73 dbm in the morning, and -76.4 during the day with yellow signal indicator (good), while in the afternoon -92,2 dbm with color signal indicator red (poor). Then the test results data in the analysis using statistical methods anova single factor. Results of data processing with this statistics obtained that helical antenna effect on the change of signal strength.   Keywords: Helical antenna, signal strength, single factor anova.